Epidemiology of Hirschsprung's Disease in Taiwanese Children: A 13-year Nationwide Population-based Study - Shu-Ti Chia; Solomon Chih-Cheng Chen; Chin-Li Lu; Shew-Meei Sheu; Hsing-Ching Kuo (Elsevier, 2016)
Hirschsprung's disease (HD) is an important colon disease in children. The aim of this study is to describe the epidemiological features of HD in Taiwanese children. Methods: We conducted a study from the Taiwan National Health Insurance Research Database and analyzed cases who received surgical intervention between 1998 and 2010 due to HD (International Classification of Diseases, 9th Revision, Clinical Modification 751.3) or megacolon (International Classification of Diseases, 9th Revision, Clinical Modification 564.7). The incidence, sex ratio, age at the surgical intervention, associated complication, and medical expenditures were analyzed. Results: There were a total of 629 HD cases, including 458 boys and 171 girls, with an overall incidence of 2.2 per 10,000 live births. The male-to-female incidence ratio was 2.38. There was no secular trend of incidence across the years. Seventy-two percent of cases received surgical treatment before the age of 1 year. The younger cases had higher operation-related medical expenditures. Those patients with preoperative enterocolitis (EC) had a higher possibility of postoperative EC than those patients without preoperative EC (34.6% vs. 24.3%, p = 0.013). There were 169 (26.9%) HD cases with additional anomalies, the most common being gastrointestinal and circulatory system anomalies. Of these, 12 (1.9%) cases were Down syndrome. Conclusion: The incidence of HD in Taiwanese children, a majority Chinese population, was one per 4545 live births with a male predominance. Preoperative EC was a significant factor that was associated with postoperative EC. The percentage associated with Down syndrome was relatively low, probably due to a prenatal screening program.